Pengaruh Marketing Mix Dan Kualitas Layanan Terhadap Keputusan Pembelian Produk Sika - Maria Widjajanti; Bruno Hami Pahar (BIP's JURNAL BISNIS PERSPEKTIF, 2021)
The purpose of this study was to determine the effect of product quality, price,promotion, service quality, and distribution on purchasing decisions of Sikaproducts at PT Adya Mandala Persada Surabaya. The sampling method used waspurposive sampling using questions in the questionnaire distributed to 125respondents who were all consumers of PT Adya Mandala Persada Surabaya.Data processing was performed using SPSS version 20.0. The results showed thatin the Validity Test all statement items were declared valid, and in the ReliabilityTest it was said that all variables were declared reliable. The results of theClassical Assumption Test show that all the requirements have been met to carryout the Multiple Linear Regression Test. From the results of the Multiple LinearRegression Test, the value of Y = 2.399 - 0.067X1 + 0.081X2 + 0.217X3 +0.234X4 + 0.697X5 is obtained. The result of the Determinant Coefficient Testshows that the Adjusted R Square is 54.9%, meaning that all X variables have amoderate contribution. The t test results get the following values: (i) variable X1= tcalculate -0.785 < ttable 1.980 with a significance level of 0.434 > 0.05, meaningthat product quality has no effect on purchasing decisions; (ii) variable X2 =tcalculate 0.793 < ttable 1.980 with a significance level of 0.429 > 0.05, which means that the price has no effect on purchasing decisions; (iii) variable X3 = tcalculate 2,564 > ttable 1,980 with a significance level of 0.012 < 0.05, it means that promotion has a significant effect on purchasing decisions; (iv) variable X4 =tcalculate 3.024 > ttable 1.980 with a significance level of 0.03 < 0.05, it means thatservice quality has a significant effect on purchasing decisions; (v) variable X5 =tcalculate 6,063 > ttable 1,980 with a significance level of 0,000 < 0.05, it means that the distribution has a significant effect on purchasing decisions. Overall it can be concluded that product quality and price have no effect on purchasing decisions while promotion, service quality, and distribution have a significant effect on purchasing decisions.